Perbandingan Metode Latihan Interval Ekstensif dan Intensif Terhadap Peningkatan Daya Tahan Aerobik - Mochamad Zakky Mubarok; Yudhi Kharisma (Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2021)
Aerobic endurance is a person's physical ability. Appropriate exercise methods are needed in improving physical conditions, especially aerobic endurance as an effort to develop and train the process. The purpose of this study is the application of extensive interval training methods and intensive interval training methods in increasing aerobic endurance. This research uses experimental research method with research design using nonequivalent control group design. The instrument used to determine aerobic endurance is a Multi-StageTest (Bleep Test). The subjects who participated in this study were 30 students from one of the Health and Recreation Physical Education study programs in Region 3 West Java using purposive sampling technique. The results of the study stated that: (1) Extensive interval training methods had an effect on increasing aerobic endurance. (2) Interval training method that has an effect on increasing aerobic endurance. (3) The interval training method that gives a better effect than the extensive interval training method on increasing aerobic endurance concludes that the intensive interval training method is better than the extensive interval training method